Expression of feeding-related neuromodulatory signalling molecules in the mouse central olfactory system - Nogi, Yasuko (Sci Rep, 2020)
Various neural systems cooperate in feeding behaviour, and olfaction plays crucial roles in detecting and evaluating food objects. While odour-mediated feeding behaviour is highly adaptive and influenced by metabolic state, hedonic cues and learning processes, the underlying mechanism is not well understood. Feeding behaviour is regulated by orexigenic and anorexigenic neuromodulatory molecules. However, knowledge of their roles especially in higher olfactory areas is limited. Given the potentiation of feeding behaviour in hunger state, we systemically examined the expression of feeding-related neuromodulatory molecules in food-restricted mice through quantitative PCR, in the olfactory bulb (OB), olfactory tubercle (OT), and remaining olfactory cortical area (OC). The OT was further divided into attraction-related anteromedial, aversion-related lateral and remaining central regions. Examination of 23 molecules including neuropeptides, opioids, cannabinoids, and their receptors as well as signalling molecules showed that they had different expression patterns, with many showing elevated expression in the OT, especially in the anteromedial and central OT. Further, in mice trained with odour-food association, the expression was significantly altered and the increase or decrease of a given molecule varied among areas. These results suggest that different olfactory areas are regulated separately by feeding-related molecules, which contributes to the adaptive regulation of feeding behaviour.